Psychiatric ethical issues of transgender people - A. Ya. Perekhov; M. N. Kryuchkova (Медицинский вестник Юга России, 2022)
Today, psychiatric care for people with transgender people in the Russian Federation is difficult due to non-compliance with ethical principles in the work of the psychiatric service. The article deals with the unresolved ethical conflict regarding gender reassignment procedures between proponents of "not allowed, forbidden" with the attitude of psychiatrists to issue permission for sex reassignment only to "real" transsexuals, and supporters of the opposite liberal attitude towards issuing permission. for gender reassignment procedures for almost all applicants. Our article discusses ethical issues to help transgender people. The ethical principles of autonomy, harmlessness and beneficence in this article are intended to help transgender people. The authors ethically write about adding and not adding a transgender diagnosis to the International Classification of Diseases. This article raises concerns about the benefits and harms, the principle of respect for autonomy and the principle of beneficence, in order to provide good quality ethical care for transgender people. The authors discuss the problem of the ethical attitude of a psychiatrist to the mental health of transgender subjects. The authors discuss the ethical problem of the psychiatrist's attitude to the mental health of transgender subjects, medicalization and medical paternalism with the help of transgender people. This article raises considerations about the ethical role of the psychiatrist in gender reassignment procedures for subjects with varying degrees of mental health. The authors propose an algorithm for providing psychiatric care to persons who have undergone gender reassignment, which includes an in-depth examination by psychiatrists, psychologists, sexologists and a collegial conclusion on the state of mental health of a transgender person in the triad: mentally healthy or "have mental disorders", "borderline" or "mental psychotic disorders".